Cold Weather Field Evaluation of the 18-Man Arctic Tray Pack Ration Module, the Meal, Ready-to-Eat, and the Long Life Ration Packet - King, Nancy; Mutter, Susan H.; Robert, Donald E. (1993)
The Army Field Feeding System was evaluated for its ability to provide adequate nutrition and hydration during a 10-day cold weather field exercise. Soldiers consumed the 18-Man Arctic Tray Pack Ration Module with either a wet-pack (Meal, Ready-to-Eat) or a dehydrated (Long Life Ration Packet) individual ration. Both feeding regimens were acceptable, meeting protein and micronutrients requirements. However, the soldiers consumed only 70% of their energy requirement, thus losing an average of 0.9% of body weight. This weight loss, although not excessive, underscores the importance of maintaining an adequate food intake during extended cold weather military field operations.